Enhanced Meiyu‐Baiu Rainfall in Early Summer 2020: Aftermath of the 2019 Super IOD Event. Issue 22 (23rd November 2020) - Takaya, Yuhei; Ishikawa, Ichiro; Kobayashi, Chiaki; Endo, Hirokazu; Ose, Tomoaki
Abstract: In early summer 2020, the Meiyu‐Baiu rainfall was markedly enhanced, triggering devastating floods in Japan and central China. We examined the underlying processes using a climate model and analysis. The enhanced Meiyu‐Baiu rainfall was reasonably predicted by the climate model initialized at the end of April. The sensitivity experiment indicated that Indian Ocean (IO) warming enhanced the Meiyu‐Baiu rainfall. Moreover, we found that the warm IO condition can be traced back to the super Indian Ocean Dipole (IOD) in 2019. The IO warmth was influenced by successive processes: record strong downwelling Rossby waves excited by the IOD and tripole sea surface temperature anomalies in the tropical IO‐western Pacific, their arrival to the southwestern IO in spring, and associated modulation of monsoon flow. The results suggest that the seasonal predictability of the Meiyu‐Baiu rainfall in 2020 originated from the super IOD. Plain Language Summary: In early summer 2020, Japan and central China suffered from serious floods due to torrential rainfall associated with the intensified Meiyu‐Baiu front, which extends from central China to southern Japan. The results of climate model simulations indicated that a warm condition of the Indian Ocean (IO) was an underlying condition for the enhanced rainfall. We found that the warm IO condition can be traced back to the strong Indian Ocean Dipole (IOD) episode in 2019, which featured a pair of colder‐than‐normal and warmer‐than‐normal ocean temperatures west of the Sumatra coast and in the western IO, respectively. This IOD contributed to the IO warming in the following seasons through oceanic dynamics and monsoon modulation. Key Points: The markedly enhanced rainfall in the Meiyu‐Baiu frontal zone in early summer 2020 was associated with the warm IO condition The warm IO condition can be traced back to the super IOD event in 2019 Ocean dynamics and associated modulation of monsoon flow in the IO sector facilitated IO warming